Going global, going digital: Firm internationalisation and digital resource use - Pascal Mayer (Universität Münster, Institut für Organisationsökonomik, 2025)
This research paper explores the relationship between firm internationalisation and digital resource use. On the one hand, the modularity of digital resources and their applicability in different international contexts provide significant benefits to multinational companies. On the other hand, the complexity of managing digital resources across different institutional systems escalates with rising levels of internationalisation. Because of these competing forces, I argue that the relationship is inversely U-shaped. Additionally, I investigate the moderating effect of firms' financial constraints and conjecture a steepening effect of the inverted Ushape. In my empirical identification strategy, I employ a text-based measure of internationalisation, based on companies' 10-K annual reports, and combine this measure with data on internet and e-commerce technology used by Standard & Poor's 1,500 firms. The results provide empirical support of an inverse U-shaped relationship and the moderating role of financial constraints. Various robustness tests corroborate the findings. This study contributes to the literature streams of firm internationalisation and information systems research by highlighting the trade-offs faced by MNEs when they "go digital". – – Diese Studie untersucht den Zusammenhang zwischen der Internationalisierung von Unternehmen und der Nutzung digitaler Ressourcen. Einerseits bieten die Modularität digitaler Ressourcen und ihre Anwendbarkeit in verschiedenen internationalen Kontexten erhebliche Vorteile für internationale Unternehmen. Andererseits nimmt die Komplexität der Verwaltung digitaler Ressourcen über verschiedene institutionelle Systeme hinweg mit zunehmenden Internationalisierungsgrad zu. Aufgrund dieser konkurrierenden Kräfte argumentiere ich, dass sich die Beziehung durch ein umgekehrtes U beschreiben lässt. Darüber hinaus untersuche ich die moderierende Wirkung von finanziellen Beschränkungen und vermute eine Streckung des Zusammenhangs. In der empirischen Identifikationsstrategie verwende ich ein textbasiertes Maß zur Messung der Internationalisierung von Unternehmen, das auf 10-K-Jahresberichten US-amerikanischer Unternehmen des S&P 1.500 Index basiert, und kombiniere dieses mit Daten zu Internet- und E-Commerce-Technologien sowie Buchhaltungs- und Finanzkennzahlen. Die Ergebnisse unterstützen die Hypothesen einer umgekehrt U-förmigen Beziehung sowie der Moderation durch finanzielle Beschränkungen. Mehrere Robustheitstests untermauern die Ergebnisse. Diese Studie leistet einen Beitrag zur Literatur im Bereich der Unternehmensinternationalisierung und Informationssysteme, indem sie Zielkonflikte aufzeigt, denen sich multinationale Unternehmen gegenübersehen, wenn sie digitalisieren.
Keywords: F20; F23; M16; O33; 650; Digital Resources; Digital Strategic Initiatives; Financial Constraints; FirmInternationalisation; Multinationals